Review of the Commission for Children and Young People Act 1998 and the Child Protection (Prohibited Employment) Act 1998 report to the Hon Carmel Tebbutt MLC Minister for Youth - L'Orange, Helen (Sydney : NSW Commission for Children & Young People, 2004)
This report reviews and makes recommendations under the two acts for improvements to the Commission and endorses the need for national co-operation for the protection of children in employment.
"November 2004"
Title from title screen (viewed 19/04/2006).
Mode of access: Internet via the World Wide Web. On 19/04/2006 available from: http://www.kids.nsw.gov.au/files/Leg_Review_CCYP.pdf
System requirements: Adobe Acrobat Reader to access files in PDF format
Selected for archiving
Keywords: New South Wales; New South Wales; Child abuse -- Law and legislation -- New South Wales; Child abuse -- New South Wales -- Prevention; Child labor -- Law and legislation -- New South Wales; Child molesters -- Legal status, laws, etc -- New South Wales; Labor laws and legislation -- New South Wales